Environmental change and migration: perspectives for future action - Benjamin Schraven (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
The issue of what links exist between environmental change and migration has been attracting increasing attention both in the media and in the scientific community in recent years. There is still a lot of uncertainty about how exactly environmentally induced migration and its effects should be defined. Nonetheless, the results of several large international research projects allow some conclusions to be drawn as regards the link between environmental change and migration: Migration is rarely caused by ecological factors alone. In the vast majority of cases, it is the result of a complex interplay between political, social, economic and ecological factors. In areas facing creeping or rapidly occurring environmental changes, migration is an adaptation rather than a survival strategy. Migration that takes place in the context of environmental change largely occurs within national borders or sub-regions but not between continents. For some time now, many discussions have been held about the possibility of improving the protection under (public international) law of persons who consider themselves as having been forced to migrate in the context of ecological changes. But neither the option to extend the Geneva Convention relating to the Status of Refugees by an ecological component nor the possibility to create an autonomous legal instrument for this group of forced migrants appears to be especially promising in this regard. There is a problem of coherence at the international cooperation level: while some international organizations are very actively addressing the issue of environmental change and migration, others are virtually completely ignoring it. Even during the international climate negotiations, the issue was first taken up only starting in 2010 in Cancún. However, the link between environmental change and migration has so far only represented a marginal aspect of the climate negotiations. In many countries affected by environmental change, there is a clearly recognisable tendency to consider internal migration as a phenomenon that is important to prevent, or at least mitigate against. Thus, for example, many (planned) measures for adapting to climate change are understood to stem migration. Based on the findings on the link between environmental change and migration, the appreciation of the problem at the international and national levels and the international legal situation, six areas in which action should be taken may be identified: Instead of extending the Geneva Convention relating to the Status of Refugees or creating a separate convention for “environmental migrants”, existing legal instruments should be strengthened. The relevant UN and non-UN organisations from the areas of development, environment, climate, migration and humanitarian aid should create an international coordination unit for migration. “Migration management” (e.g. by providing relevant information for migrants) instead of migration prevention should be pursued. Both urban as well as rural living conditions should be improved. Migrants and population groups affected by environmental change – many live in marginal situations – should be involved in decision-making and planning processes.
Keywords: 330; Klimawandel; Regionale + globale + transnationale Governance